Perancangan Komik Web tentang Edukasi Dampak Negatif Judi Daring bagi Dewasa Muda - Sunarso, Christina Amelia; Aryani, Dewi Isma; Wianto, Elizabeth (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
Internet connectivity and social media have evolved into valuable tools for people in the contemporary digital era to receive information and interact socially. Unfortunately, many people continue to exploit these services to promote and even play online gambling, exposing internet andsocial media userstoads. According to the poll results, practically all internet users have been exposed to online gambling marketing on social media. Several factors influence respondents' decisions to receive information about the detrimental effects of online gambling, including their visual style preferences, awareness, and willingness to be informed. One solution to the challenges listed above is through education and outreach in the form of web comic media, which are widely available and easy to access by the general public, particularly young adults, while also serving as a practical amusement medium. Web comics' tales are broken into short episodes based on societal allusions and true stories. It is intended that by using web comics to educate people about the bad effects of online gambling, it will assist discourage individuals from participating in online gambling and communicate information to authorities for victims of online gambling.